Medical waste management practices in a selected secondary healthcare facility - Sarker, Mohammad Ferdous Rahman; Debnath, Rupa; Rahman, AFM Shahidur; Howlader, Liton Bhushan; Sarker, Zakia Jalal; Rahman, Md Shafiur (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Introduction: Living things and human activities produce huge waste every day. Globally medical waste is the second most hazardous waste after radiation waste. In this context, this study was a modest endeavor to examine the current situation of ‘Jamalpur 250 Bed General Hospital’s’ medical waste management practice. Methods : This cross sectional study was conducted among doctors, nurses, laboratory technicians and sanitary staffs at ‘Jamalpur 250 Bed General Hospital’. 185 healthcare personnel were purposively interviewed (face to face) to assess previous and existing knowledge and practices of medical waste management. Informed written consent was taken from the study subjects before taking interview. Data was collected by a pretested semi-structured questionnaire. Results : In our current study, out of 185 respondents, 10.0% were doctors and 43.0% were nurses. Five among six color coding segregation system, below 50.0% of the respondent answered correctly. Only 23.8% respondents revealed that the waste handler use PPE properly. 90.8% respondents were mentioned about the lack of storage place for medical waste at hospital premise. 55.7% respondents didn’t know about the in house disinfection process, 56.8% respondents didn’t know about the municipal vehicle support and 52.4% didn’t know about the availability of waste management equipment. Poor knowledge with favorable attitude and risky medical waste management practice of this hospital’s healthcare personnel were detected. Conclusion : This study were indicated that the majority of healthcare personnel did not apply the recommended medical waste management practice set by WHO. Moreover, the current medical waste management practice in selected district hospital was not managed properly and could pose a risk for human health and the environment. J Bangladesh Coll Phys Surg 2020; 38(4): 160-165